Роль та місце вищої освіти України в сучасній економічній системі - Сало, А. В.; Salo, A. (КНТУ, 2014)
В статті розглянуто та розширено поняття вищої освіти, проведений аналіз вищої освіти в контексті глобалізації українського суспільства. Обґрунтовано взаємозв’язок та залежність роботи інституту вищої школи України з економічним зростанням країни. Розглянуті та конкретизовані головні проблеми сфери вищої освіти України. Представлений аналіз впливу недоліків вищої освіти на загальноекономічну ситуацію в державі. Запропонована низка можливих шляхів подолання головних проблем в системі вищої освіти України. Taking into account rapid development of all spheres of the country in light of the recent globalization trends, it is impossible not to notice substantial retardation of all sub-systems of higher education. This condition is one of the major subsystems of the country is threatening and extremely dangerous. Despite the fact that the education system provides the country with such essential resources as intellectual capital, labor and scientific potential, modernization of this system through the reconsideration and resolve urgent problems is obvious etc.
The role and place of higher education of Ukraine in modern economic system
Keywords: вища освіта; глобалізація; сучасна система; інтеграція системи вищої освіти України; економічна система; higher education; globalization; modern; integration of higher education in Ukraine; economic system